Eight Days of Earth Reambulation Worsen Bone Loss Induced by 1-Month Spaceflight in the Major Weight-Bearing Ankle Bones of Mature Mice - Gerbaix, Maude; White, Heather; Courbon, Guillaume; Shenkman, Boris; Gauquelin-Koch, Guillemette; Vico, Laurence (Frontiers in Physiology, 2018)
Spaceflight induces bone alterations with site-specific rates of bone loss according to the weight-bearing function of the bone. For the first time, this study aimed to characterize bone microarchitecture and density alterations of three ankle bones (calcaneus, navicular, talus) of mice after spaceflight and to evaluate the impact of eight days of Earth reambulation. Ten C57BL/6N male 4-month old mice flew on the Bion-M1 biosatellite for one month; half were euthanized within 24-hours of return and half after 8-days recovery on Earth. Bone microarchitecture and quality was assessed by microtomography (µCT). Whole calcaneus bone volume fraction decreased in Flight group (-6.4%, p<0.05), and worsened in the Recovery group (-11.08%, p<0.01), when compared to Control group. Navicular and talus trabecular bone volume fraction showed trends towards decrease in Flight and differences reached statistical significance in Recovery group (-8.16%; -8.87%, respectively; p<0.05) when compared to Control group. At calcaneus, cortical thickness decreased in Recovery vs Control groups (-11.69%; p<0.01). Bone surface area, reflecting periosteal bone erosion, significantly increased in all bone sites analyzed. Qualitative analyses of 3-D bone reconstruction revealed local sites of cortical thinning and bone erosion, predominantly at articulations, muscle insertions, and ground contact bone sites. Overall, spaceflight-induced bone loss in ankle bones was site and compartment specific whilst the tissue mineral density of the remaining bone was preserved. Eight days after landing, bone status worsened as compared to immediate return.